Faktor Penentu Tingkat Pengangguran Provinsi Kepulauan Riau - Erlangga Rajid; Fafurida (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The dynamics of the region's labour market are called into question by the continually higher open unemployment rate in the province of Riau Islands compared to the national average. Using the years 2017–2023, this study looks into the causes of open unemployment in the province of Riau Islands. With an emphasis on the function of public spending, ease of access to technology, and GDP expansion. Using Eviews 12 software's FEM specification test and a quantitative method, this study evaluates secondary data provided from Statistics Indonesia (BPS) of the Riau Islands Province using panel data regression analysis. Government spending significantly lowers the open jobless rate, whereas technological advancement and economic progress significantly raise it. Based on these results, the Riau Islands Province needs effective policies to lower the open unemployment rate, maximise the use of government funds, and tap into the possibilities of technological access and economic growth.